Étude chez l'huître creuse, Crassostrea gigas, des anomalies génomiques provoquées par l'exposition à des concentrations environnementales de diuron : caractérisation des atteintes, étude de leur héritabilité et conséquences pour la survie et la croissance des naissains - Barranger, Audrey (Université de Nantes Angers Le Mans, 2015)
The aims of this PhD were to determine (1) the effects of the herbicide diuron on the genome of the oyster, Crassostrea gigas, (2) the possible transmission to the offspring of damaged DNA and (3) its consequences on oyster physiology. The genotoxicity of diuron and the vertical transmission of DNA damage were highlighted after parental exposure to environmental concentrations of diuron during the gametogenesis. Primary DNA lesions were detected in both somatic cells and germ cells of exposed genitors. Detection of the oxidized base 8-oxodGuo in gonads shows that exposure to diuron led to an oxidative stress which likely explains the observed DNA strand breaks in spermatozoa. The transmission of these DNA damage was confirmed by fluorescent in situ hybridization: aneuploid nuclei were detected in embryos from diuron-exposed genitors. This hyper- and hypodiploidy particularly concerns 5S and 18-5.8-28S ribosomal genes localized on chromosomes 4, 5 and 10. Flow cytometry analysis showed survival of hypodiploid individuals at spat stage. This vertical transmission of damaged genetic material is associated with deleterious effects on the physiology of the offspring (developmental defects, growth retardation). Data acquired during this PhD contribute to a better understanding of the long-term effects of exposure to genotoxic pollutants. In the context of massive mortality outbreaks, the presence of chemical pollutants may contribute to a weakening of oysters in case of the presence of pathogens or adverse physicochemical environmental conditions. les effets d’un herbicide, le diuron, sur le génome de l'huître creuse, (2) la possible transmission des dommages à l'ADN à la descendance ainsi que (3) les conséquences physiologiques associées. La génotoxicité du diuron et la transmission verticale des dommages à l'ADN ont été démontrées après une exposition parentale à des concentrations environnementales de diuron pendant la période de gamétogenèse. Des lésions primaires à l’ADN ont été détectées aussi bien dans les ...